Teachers and the development of historical thinking based on controversial topics: a look at Chilean History classrooms - Torres, Bastián; Muñoz Labraña, Carlos (Clio. History and History Teaching, 2024)
This study presents preliminary findings from doctoral research on history teachers and their development of historical thinking. The primary objective was to characterise and analyse classroom practices that address the ethical dimension of historical thinking, particularly in relation to controversial topics such as the occupation of Araucanía. Using qualitative content analysis, eleven transcripts from first-year secondary school classes, taught by three history teachers, were examined. The findings indicate that, although teachers provide explanations that contextualise the historical period under study, they often fail to encourage the development of nuanced ethical judgments from a historical perspective regarding past actions.